From TNF-induced signaling to NADPH oxidase enzyme activity: Methods to investigate protein complexes involved in regulated cell death modalities - Ladik, Maria; Valenta, Hana; Erard, Marie; Vandenabeele, Peter; Riquet, Franck B. (Frontiers in Cell Death, 2023)
The formation of molecular complexes is a key feature of intracellular signaling pathways which governs to the initiation and execution of dedicated cellular processes. Tumor Necrosis Factor (TNF) and Reactive Oxygen Species (ROS) function as signaling molecules and are both involved in balancing cell fate decision between cell survival or cell demise. As master regulators of cell signaling, they are also instrumental in controlling various cellular processes towards tissue homeostasis, innate immunity and inflammation. Interestingly, TNF and ROS are interlinked and involved in regulating each other’s production via the engagement of molecular signaling complexes. This relationship calls for detailed reviewing of both TNF-induced and ROS-producing molecular complexes in the context of regulated cell death (RCD) modalities. Here, we outline biotechnological approaches that were used to investigate the TNF- and, concerning ROS, the NADPH oxidase-related molecular complexes with an emphasis on different regulated cell death modalities. This systematic review highlights how the cell death field has benefited from both biochemical and live-cell fluorescence imaging approaches. This knowledge and established workflows are highly generalizable, can be of a broader use for any protein-complex studies, and well suited for addressing new challenges in signaling dynamics. These will help understand molecular signaling complexes as ensembles organized into signaling platforms, most likely the key sites of signaling dynamics integration toward cell fate regulation.